Terrorism, Geopolitics, and Multinational Security Cooperation in Central Asia (American Journal of Islam and Society, 2006)
On 22-24 February 2006, the Asia-Pacific Center for Security Studies(APCSS) held this conference on the complex security environment ofCentral Asia as the region continues to struggle with the phenomena of terrorismand religious extremism, poverty and corruption, political instabilityand authoritarian governance, as well as great power (China, Russia, and theUnited States) suspicion and rivalry. These challenges are not uniquelyCentral Asian, but the region seems to be particularly vulnerable to them asits young nations are undergoing a significant political, social, and economictransformation. How the region copes with these issues will extend importantlessons to the world as a whole.This forum examined the trilemma posed for Central Asia and thebroader Asia-Pacific region. First, for the war on terror in the region to besuccessful, it must evolve into well-implemented stabilization and reconstructionefforts as well as dramatic improvements in governance andhuman rights. Second, no country on its own can alter the situation inCentral Asia, for such an effort requires cooperation between all of the majorpowers and stakeholders in the region (India, Iran, Pakistan, and Turkey).The magnitude of the problem of terrorism, which affects most if not allcountries in the region, should preclude another variation of the Great Game.Finally, while the number of regional organizations and security forums inCentral Asia has been growing, the low degree of coordination among themtriggers counterproductive rivalries and plays into the hands of extremistelements. Since terror knows no borders, what happens in Central Asia significantlyimpacts developments elsewhere.Although the counterterrorist effort in Central Asia has successfullymarginalized the Taliban and al-Qaeda, the localization of the terrorist threatmeans that new autonomous extremist cells continue to emerge in CentralAsia. The sources of proliferation of radical Islam can be found in socioeconomicdeprivation, widespread corruption, and political ...